THE INFLUENCE OF SERVICE QUALITY AND BRAND IMAGE ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE AT PT. TOYOTA HASJRAT ABADI MUTIARA IN PALU CITY - Indriany, Indriany; P. Adam, Rosida; Ponirin, Ponirin (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2022)
This research aims to find out the influence of service quality and brand image on customer loyalty with customer satisfaction as an intervening variable atPT. Toyota Hasjrat Abadi Mutiara Palu. The population consists of customers in Palu City who use the PT. Toyota Hasjrat Abadi Mutiara Palu. This type of research is explanatory research using a quantitative approach with a total sample of 120 respondents. The data analysis technique used was Partial Least Square (PLS) with the sampling technique using the structural Equation Modeling (SEM) method. The results of the research show that service quality has a positive and insignificant influence on customer loyalty, brand image has a positive and significant influence on customer loyalty, service quality has a positive and significant influence on customer satisfaction, brand image has a positive and significant influence on customer satisfaction, customer loyalty has a positive and significant influence on customer satisfaction, service quality through customer satisfaction has a positive and significant influence on customer loyalty, and brand image through customer satisfaction has a positive and significant influence on customer loyalty. Keywords: ServiceQuality, Brand Image, Customer Loyalty, Customer Satisfaction.